Argentine exports: long run behavior and dynamics - Ahumada, Hildegart (1994)
Argentine exports at aggregate level have been very difficult to model. Indeed, it is usual to think that total exports are the result of adding quite different items, at least agricultural and “non- traditional” ones, which respond to special determinants. From a macroeconomic perspective, however, one can be interested in looking for the “common factors” behind them - visual inspection of the time- behavior of these aggregates suggests they may be present. An econometric modelling based on this view appears to be critical when issues like the effect of opening up the economy, the relationship with growth and the response to exchange rate, etc Argentina are part of currant debate.